The Response of Phagocytes to Indoor Air Toxicity - Vilén, Liisa K.; Atosuo, Janne; Lilius, Esa-Matti (Frontiers in Immunology, 2017)
This Perspective presents a viewpoint on potential methods assessing toxicity of indoor air. Until recently, the major techniques to document mouldy environment have been microbial isolation using conventional culture techniques for fungi and bacteria as well as in some instances polymerase chain reaction (PCR) to detect microbial genetic components. However, it has become increasingly evident that bacterial and fungal toxins, their metabolic products and volatile organic substances (VOCs) emitted from corrupted constructions are the major health risks. Here, we illustrate how phagocytes, especially neutrophils can be used as a toxicological probe. Neutrophils can be used either in vitro as probe cells, directly exposed to the toxic agent studied, or they can act as in vivo indicators of the whole biological system exposed to the agent. There are two convenient methods assessing the responses, one is to measure chemiluminescence emission from activated phagocytes and the other is to measure quantitatively by flow cytometry the expression of complement and immunoglobulin receptors on the phagocyte surface.